External Validation of the Adult Spinal Deformity (ASD) Frailty Index (ASD-FI) in the Scoli-RISK-1 Patient Database. Issue 20 (15th October 2018) - Miller, Emily K.; Lenke, Lawrence G.; Neuman, Brian J.; Sciubba, Daniel M.; Kebaish, Khaled M.; Smith, Justin S.; Qiu, Yong; Dahl, Benny T.; Pellisé, Ferran; Matsuyama, Yukihiro; Carreon, Leah Y.; Fehlings, Michael G.; et al.
Abstract : Study Design: Analysis of a prospective multicenter database. Objective: To assess the ability of the recently created Adult Spinal Deformity (ASD) Frailty Index (ASD-FI) to predict odds of major complications and length of hospital stay for patients who had more severe preoperative deformity and underwent more invasive ASD surgery compared with patients in the database used to create the index. Summary of Background Data: Accurate preoperative estimates of risk are necessary given the high complication rates currently associated with ASD surgery. Methods: Patients were enrolled by participating institutions in Europe, Asia, and North America from 2009 to 2011. ASD-FI scores were used to classify 267 patients as not frail (NF) (<0.3), frail (0.3–0. 5), or severely frail (SF) (>0.5). Multivariable logistic regression, adjusted for preoperative and surgical covariates such as operative time and blood loss, was performed to determine the relationship between ASD-FI category and incidence of major complications, overall incidence of complications, and length of hospital stay. Results: The mean ASD-FI score was 0.3 (range, 0–0.7). We categorized 105 patients as NF, 103 as frail, and 59 as SF. The adjusted odds of developing a major complication were higher for SF patients (odds ratio = 4.4; 95% CI 2.0, 9.9) compared with NF patients. After adjusting for covariates, length of hospital stay for SF patients increased by 19% (95% CI 1.4%, 39%) compared with NF patients. The odds of developing a major complication or having increased length of stay were similar between frail and NF patients. Conclusion: Greater patient frailty, as measured by the ASD-FI, is associated with a longer hospital stay and greater risk of major complications among patients who have severe preoperative deformity and undergo invasive surgical procedures. Level of Evidence: 2